HARMONY IN THE HOME: THE MEANING OF MAPPASIKARAWA FROM AN ISLAMIC LAW PERSPECTIVE - Darwis, Rustan; Sabaruddin, Sabaruddin (Jurnal Ar-Risalah, 2025)
This study aims to understand the meaning of Mappasikarawa in Islamic law and the Mappasikarawa procession in Bugis marriage customs. This study uses a qualitative approach with ethnographic methods. The research was conducted in Boneputeh Village. Data was collected through the following techniques: a) Participatory observation. b) Interviews, c) Documentation. Data was analyzed using descriptive qualitative analysis and thematic analysis, with the following stages: a) Transcription and coding, b) Data reduction. c) Data interpretation, d) Data validity. The results of the study show that the Mappasikarawa tradition is a very important form of traditional ceremony in the social life of the Bugis people, especially in relation to the marriage process. This ceremony is carried out as a series of events after the marriage contract has been concluded. Mappasikarawa aims to guide the bride and groom in building a new household. The Mappasikarawa ceremony has deep ritual, spiritual, and educational values, where every action, advice, and prayer given has a symbolic meaning that reflects family life. From a sociocultural perspective, Mappasikarawa demonstrates the close relationship between traditional practices and efforts to maintain social harmony. The implementation of this ritual involves various elements of society, including traditional leaders, immediate family, and relatives, who together instill moral values. In the implementation of Mappasikarawa, there are several parts of the body that may be touched, each touch having a meaning closely related to religious teachings.